Fallibilism and mathematics in Charles S. Peirce - Salatiel, José Renato (Argumentos - Revista de Filosofia, 2009)
The Charles Sanders Peirce’s doctrine of fallibilism states that by means of reasoning, we can never achieve certainty, accuracy and universality absolutes. If is haven’t any conclusive inferences from likely, would infallibility when it comes to mathematical propositions of type 2 +2 = 4? Scholars of the American philosopher are not unanimous about this issue. This article discusses the hypothesis that there is a logic certainty inherent of the mathematical judgments, which, however, does not conform to an epistemological certainty. What is the fallibility asserts is the impossibility of an axiomatic when dealing with questions about fact, but the math does not say anything of real unless about hypothetical things. But it is fallible in its experimental character that Peirce explained in the division between corollarial and theorematic deductions.